Assessment of Eurocode shear design provisions for cold-formed steel sections. (January 2023) - Gatheeshgar, Perampalam; Bock, Marina; Chandrasiri, Dilanka; Suntharalingam, Thadshajini
Abstract: Cold-formed steel (CFS) sections are widely used in structural systems and are particularly prone to shear failure in short span applications. Therefore, accurate shear strength estimation is essential for the design. However, while there exists an abundance of research studies investigating the shear behaviour of CFS sections, there is a clear need for the assessment of Eurocode 3 shear design provisions. Towards meeting this need, the design of CFS sections subjected to shear is studied herein. Existing experimental data on CFS lipped channels and hollow flange sections were assembled from the literature. The collected experimental data was then used to assess the accuracy of the current Eurocode 3 shear design provisions. The current Eurocode 3 design provisions are shown to provide overly conservative shear strength predictions against the experimental data. Modifications, including the slenderness of the cross-section to reflect the shear buckling coefficient were proposed. The proposed modifications to the current design provisions offer substantially improved accuracy in shear strength predictions.